Financial access in post-reform India - Bhavani, T. A.; Bhanumurthy, N. R. (New Delhi ; Oxford : Oxford University Press, 2012)
Using a macroeconomic growth approach, this text focuses on two important aspects of the Indian financial sector-development and access.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Financial services industry -- India; Finance -- India